1998
DOI: 10.1095/biolreprod59.6.1334
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of the α1 to α6 Chains of Type IV Collagen in Bovine Follicles1

Abstract: During follicular development the proliferative and differentiated state of the epithelioid granulosa cells changes, and the movement of fluid across the follicular basal lamina enables the formation of an antrum. Type IV collagen is an important component of many basal laminae. Each molecule is composed of three alpha chains; however, six different type IV collagen chains have been identified. It is not known which of these chains are present in the follicular basal lamina and whether the type IV collagen com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
38
0
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 32 publications
8
38
0
1
Order By: Relevance
“…Collagen IV presented in the theca layer of the follicle, with more intense staining detected in later stage follicles and older ovaries. These observations are consistent with staining in the rat (Bortolussi et al 1989;Frojdman et al 1998) and bovine (Zhao and Luck 1995;Rodgers et al 1998;IrvingRodgers et al 2002). Laminin also stains the basal lamina in the pig and rabbit (Lee et al 1996) and type IV collagen was found in the theca of human ovaries (Iwahashi et al 2000).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Collagen IV presented in the theca layer of the follicle, with more intense staining detected in later stage follicles and older ovaries. These observations are consistent with staining in the rat (Bortolussi et al 1989;Frojdman et al 1998) and bovine (Zhao and Luck 1995;Rodgers et al 1998;IrvingRodgers et al 2002). Laminin also stains the basal lamina in the pig and rabbit (Lee et al 1996) and type IV collagen was found in the theca of human ovaries (Iwahashi et al 2000).…”
Section: Discussionsupporting
confidence: 81%
“…In the bovine, ECM composition varies during growth ) and changes during atresia (Irving-Rodgers et al 2002). The ECM in the ovary has been characterized for several species, such as bovine (Zhao and Luck 1995;Rodgers et al 1998;McArthur et al 2000;Rodgers et al 2001), human (Yamada et al 1999;Iwahashi et al 2000), rat (Rajah et al 1994;Frojdman et al 1998), ovine (Huet et al 2001;Le Bellego et al 2002), and equine (Gentry et al 1996), with type I collagen, type IV collagen, fibronectin, and laminin the most commonly examined ECM proteins (Bortolussi et al 1989;Rajah et al 1994;Figueiredo et al 1995;Zhao and Luck 1995;Huet et al 1997). The mouse has been a widely used model to examine folliculogenesis in vivo (Matzuk 2000) and in vitro (Cortvrindt and Smith 1998;Spears et al 1998;O'Brien et al 2003;Kreeger et al 2005;Kreeger et al 2006), yet the mouse ovarian ECM has not been well described relative to other species.…”
Section: Introductionmentioning
confidence: 99%
“…5, some collagen type IV a-chains were immunohistochemically examined to reveal any changes in the major components of the basement membranes (Rodgers et al 1998, Nakano et al 2007). However, no apparent differences in the collagen a-chains were observed in the antral follicles between the PCO model and control mice (Fig.…”
Section: Histological Examination Of Mouse Ovaries After Injection Ofmentioning
confidence: 99%
“…This is not surprising as dramatic changes and remodelling of the extracellular matrix occur during ovarian follicle development (Rodgers et al 1998). The ECM is also considered as an active regulator of cell migration, division, differentiation, death and anchorage.…”
Section: Discussionmentioning
confidence: 99%
“…Thiomolybdates have also previously been shown to affect lysyl oxidase and subsequent collagen and elastin formation, often observed as symptoms of clinical copper deficiency which include cardiac problems, bone weakness and joint abnormalities (Underwood 1981). The ECM is also considered as an active regulator of cell migration, division, differentiation, death and anchorage with significant and dramatic changes in the remodelling of the extracellular matrix occurring during ovarian follicle development (Rodgers et al 1998). Collagen type IV, laminin and fibronectin are thought to be present in lamina-like material in the theca matrix and this basal lamina seems to be constantly remodelled as the follicle matures (Rodgers et al 1999).…”
Section: Introductionmentioning
confidence: 99%